Intrinsic properties and relations. Issue 8 (17th November 2018) - Plate, Jan
ABSTRACT: This paper provides an analysis of the intrinsic/extrinsic distinction, as applied both to properties and to relations. In contrast to other accounts, the approach taken here locates the source of a property's intrinsicality or extrinsicality in the manner in which that property is 'logically constituted', and thus – plausibly – in its nature or essence, rather than in e.g. its modal profile. Another respect in which the present proposal differs from many extant analyses lies in the fact that it does not seek to analyse the 'global' distinction between intrinsic and extrinsic properties on the basis of the 'local' distinction between having a property intrinsically and having it extrinsically. Instead, the latter distinction is explicated on the basis of the former.